1967
DOI: 10.2136/sssaj1967.03615995003100020035x
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Differences in Yield Response of Populus deltoides to Nitrogen Fertilization

Abstract: Trees propagated from cuttings of 22 clones of Populus deltoides were grown under unfertilized and nitrogen-fertilized conditions. Large increases in growth resulted from fertilization. A strong clone X fertilizer interaction was observed for diameter, height, and volume growth. Wood specific gravity was reduced by fertilization but no interaction between clones and fertilizers was noted for that character after 2 years.The presence of the genotype-environment interaction indicated that it would be unwise to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Verlinden et al (2013) reported that among the 12 genotype studied with genotype Hees showing the highest biomass production. Further, a strong interaction between clone (genotype) and fertilizer was observed for diameter, height and volume growth (Curlin, 1967). Such clonal differences may be the reflection of differential genetic potential of clones of favorable G×E interaction.…”
Section: Resultsmentioning
confidence: 90%
“…Verlinden et al (2013) reported that among the 12 genotype studied with genotype Hees showing the highest biomass production. Further, a strong interaction between clone (genotype) and fertilizer was observed for diameter, height and volume growth (Curlin, 1967). Such clonal differences may be the reflection of differential genetic potential of clones of favorable G×E interaction.…”
Section: Resultsmentioning
confidence: 90%
“…Clonal variation to N fertilization in poplar has been reported by Curlin (1967) who noted large differences in diameter, height and volume responses among 22 Populus deltoides clones, but the biological reasons for the differential fertilization response and nutritional balance were not explored. However, Curlin (1967) proposed that differences in root proliferation could be a genetic factor influencing mineral uptake in the juvenile period, and that physiological difference in root absorption or exchange potential might prolong growth differences in efficiency of metabolism, but no supporting evidence has been reported yet. Unfortunately, root excavations to test this hypothesis were not undertaken in this study.…”
Section: Clonal Variationmentioning
confidence: 99%
“…Research with cottonwood clones (Curlin 1967) suggests that differences among aspen clones in response to soil fertilization might be expected.…”
Section: Other Characteristicsmentioning
confidence: 99%